2020
DOI: 10.1080/09593985.2020.1737995
|View full text |Cite
|
Sign up to set email alerts
|

The Phys-Can study: meaningful and challenging - supervising physical exercise in a community-based setting for persons undergoing curative oncological treatment

Abstract: Introduction: Supervised exercise may improve physical function and quality of life during oncological treatment. Providing supervised exercise to all patients at hospitals may be impractical, with community-based settings (e.g. public gyms) as a possible alternative. To facilitate implementation, knowledge about the experiences of professionals who deliver exercise programs in community-based settings is crucial. Objective: To explore how physical therapists and personal trainers experience supervising exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…More variation in exercises has also been suggested by other studies, in order to prevent boredom, better tailor exercises to patients' preferences, needs (e.g., functional training), or capabilities, and to add exercise types other than resistance or aerobic exercises, such as balance exercises [65,71]. In addition, physical therapists and personal trainers have reported that guidance of a group of patients can be challenging (e.g., dealing with diferent types of group dynamics; providing sufcient attention to individual patients' abilities and needs) [72,73]. Tis indicates the importance of qualifed trainers and preferably small group sizes although the latter needs to be balanced with afordability.…”
Section: Refections and Opportunities To Improve Adoptionmentioning
confidence: 99%
“…More variation in exercises has also been suggested by other studies, in order to prevent boredom, better tailor exercises to patients' preferences, needs (e.g., functional training), or capabilities, and to add exercise types other than resistance or aerobic exercises, such as balance exercises [65,71]. In addition, physical therapists and personal trainers have reported that guidance of a group of patients can be challenging (e.g., dealing with diferent types of group dynamics; providing sufcient attention to individual patients' abilities and needs) [72,73]. Tis indicates the importance of qualifed trainers and preferably small group sizes although the latter needs to be balanced with afordability.…”
Section: Refections and Opportunities To Improve Adoptionmentioning
confidence: 99%